2020
DOI: 10.1002/brb3.1843
|View full text |Cite
|
Sign up to set email alerts
|

Time will tell: Decision making in premanifest and manifest Huntington’s disease

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…Focusing on the large cohort of premanifest participants, we investigated in these patients, formally without a clinical diagnosis of HD, more motoric, functional, cognitive, and psychiatric impairments if compared to genotype negative, and, in some parts, if compared to family controls. These findings go along with other research describing prodromal phases of HD, before the onset of distinct motoric symptoms (defined as diagnostic confidence level 4) and also go along with earlier observed neurocognitive, neuropsychiatric, biomarker, and structural MRI changes with brain atrophy in premanifest HD patients [ 40 , 41 , 42 , 43 , 44 , 45 ] Recently, CSF neurofilament light protein (NfL) was identified as a potential biomarker and is elevated far before the onset in pre-HD as a sensitive measure for neurodegenerative processes, starting decades before clinical onset [ 46 ]. As a limitation, no CSF measures or neuro-imaging data were available within the investigated cohorts, so neurobiological correlates could not be identified.…”
Section: Discussionsupporting
confidence: 86%
“…Focusing on the large cohort of premanifest participants, we investigated in these patients, formally without a clinical diagnosis of HD, more motoric, functional, cognitive, and psychiatric impairments if compared to genotype negative, and, in some parts, if compared to family controls. These findings go along with other research describing prodromal phases of HD, before the onset of distinct motoric symptoms (defined as diagnostic confidence level 4) and also go along with earlier observed neurocognitive, neuropsychiatric, biomarker, and structural MRI changes with brain atrophy in premanifest HD patients [ 40 , 41 , 42 , 43 , 44 , 45 ] Recently, CSF neurofilament light protein (NfL) was identified as a potential biomarker and is elevated far before the onset in pre-HD as a sensitive measure for neurodegenerative processes, starting decades before clinical onset [ 46 ]. As a limitation, no CSF measures or neuro-imaging data were available within the investigated cohorts, so neurobiological correlates could not be identified.…”
Section: Discussionsupporting
confidence: 86%
“…In line with this, deficits in emotion recognition and emotion recognition of body language is also reduced in HD patients [10, 14] and correlated with the severity of motor symptoms [14]. Given these impairments of emotion recognition as well as difficulties understanding social norms, the high prevalence of irritability and aggression in HD [15], the known widespread brain atrophy [16], and the impairment in decision-making [4], we speculated that our manifest HD cohort would perform worse than healthy control (HC), i.e., punish more often than HC. Hence, we wanted to assess whether extensive punishment is part of the neuropsychological profile of patients with manifest HD using a costly punishment task where participants were asked in fair and unfair rounds to punish a virtual counterpart.…”
Section: Introductionmentioning
confidence: 98%
“…Neuropsychiatric abnormalities can often precede motor symptoms [1][2][3] and can be more debilitating for HD patients and their families. Several studies found impairment in decision-making [4], theory of mind [5], overcoming stimulus-response incompatibility and prepulse inhibition [6], obsessive-compulsive behaviours [7], impairment in social perception [8], and emotion processing [9,10] in HD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these are preliminary data of a small sample size only tested by a subset of olfactory functioning. Our results provide indication that apart from early behavioral and cognitive changes in HD carriers [21], olfactory dysfunction could present another nonmotor symptom of HD present in very early disease stages and that further longitudinal studies are needed.…”
Section: Discussionmentioning
confidence: 77%